2015
DOI: 10.13189/ujme.2015.030304
|View full text |Cite
|
Sign up to set email alerts
|

Using Evaporative Cooling Methods for Improving Performance of an Air-cooled Condenser

Abstract: In areas with very hot weather conditions (50 to 60℃), the temperature and pressure of the airconditioning condenser are increased considerably. This causes a decrease in the cooling capacity of the cycle and also causes an increase in the power consumption due to increased pressure ratio. In this work, an experimental and theoretical investigation has been done to improve the evaporator outlet fluid temperature through enhancing condenser performance. For this purpose, several modifications on the refrigerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some of those; the air-side modifications include adding spray water above condenser, wet pad before condenser, and water vapor nozzle in the condenser air flow. Studies on adding spray water above condenser, one of these solutions, have shown that it is an important tool for increasing cooling capacity and also reducing power consumption, especially in hot climates (Vrachopoulos et al, 2007;Alhamdo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Some of those; the air-side modifications include adding spray water above condenser, wet pad before condenser, and water vapor nozzle in the condenser air flow. Studies on adding spray water above condenser, one of these solutions, have shown that it is an important tool for increasing cooling capacity and also reducing power consumption, especially in hot climates (Vrachopoulos et al, 2007;Alhamdo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Dewasa ini, penggunaan AC semakin meningkat seiring dengan bertambahnya suhu lingkungan akibat pemanasan global. Manusia terus mengembangkan teknologi untuk menyejukkan udara yang lebih efisien karena seiring dengan berkembangnya teknologi, manusia mulai menyadari bahwa efek dari penggunaan alat pendingin ruangan dapat menyebabkan konsumsi energi tinggi (Alhamdo, 2015). AC yang digunakan menghasilkan air buangan yang berasal dari proses pengembunan (evaporasi) dan proses kondensasi (Sarbu, 2014).…”
Section: Pendahuluanunclassified
“…The average investment cost of evaporative coolers is around USD 2000 for producing a cooling effect equivalent of kW. A maximum of 10 • C reduction in the condenser temperature reduced the specific power consumption by 0.085 kW/kW of cooling [34]. The effect of evaporative coolers is maximum in dry ambient conditions producing cooling up to 10 • C and moderate under humid conditions, producing a cooling of 5 • C. A 10 • C temperature reduction produces a 40% increase in COP and a 5% temperature reduction produces a 20% improvement in COP.…”
Section: Hybrid Cooling With Vapor Compression System and Evaporative Cooling Of Condenser (Hc1)mentioning
confidence: 99%